C-Reactive Protein and Breast Cancer: New Insights from Old Molecule - Shilpa Balaji Asegaonkar; Balaji Narayanrao Asegaonkar; Unmesh Vidyadhar Takalkar; Suresh Advani; Anand Pandurang Thorat (International Journal of Breast Cancer)
Recently an association between breast cancer and inflammation has emerged as the seventh hallmark of cancer. Chronic inflammation is a key contributor in the development and progression of carcinogenesis. Inflammatory pathways play an important role in the causation of breast cancer. C-reactive protein (CRP) an acute-phase reactant inflammatory protein is synthesized in hepatocytes in response to cytokines that are released from leucocytes within the tumor microenvironment. Several epidemiological studies appraised an association of CRP with breast cancer risk with inconsistent findings. Elevated levels at the time of diagnosis of breast cancer indicate aggressiveness of the tumor. CRP is also a well-established independent prognostic marker. Breast cancer survivors with the state of chronic inflammation are at risk of recurrence and metabolic disturbances. CRP lowering agents along with chemotherapeutic drugs will improve the survival of breast cancer patients. Also, it is a risk predictor for subsequent cardiotoxicity in patients receiving chemotherapy. The present review is aimed at elucidating the role of C-reactive protein, as an inflammatory risk marker and prognostic predictor of breast cancer. It also focuses on conflicting views on the role of CRP in breast cancer and its impact on therapeutic interventions.